Negative Socio-Political Gender constructs limit executive domain for Women in Administration. Need for Gender Neutral Management Policies and Practices - Masood, Farah (Journal of Pakistan Administration, 2020)
Gender discrimination and disparity is a prominent feature in Pakistani society. Patriarchal values embedded in local traditions and culture limit women's social, economic and political rights which lead to Pakistan's poor performance on various global parameters. Pakistan ranks 150th among 178 countries on Human Development Index (HDI)1and it is 148th among 149 countries on Global Gender Gap Index.2 The major part of human development gap is because of gender gap as women lag far behind men in almost all development indicators.3 Women face hostility, violence and discrimination owing to the stereotypical assumptions about their inferiority relative to men. Gender imbalance is not only a pressing moral and social issue but also a critical economic challenge. If women - who account for half the country's population - do not achieve their full economic potential, the economy suﬀers. McKinsey Global Institute estimated in a study that in a “full potential” scenario in which women play an identical role in labour markets to that of men, as much as $28 trillion, or 26 percent, could be added to global annual GDP by 2025.4 In Pakistan women empowerment is viewed essentially as a Western value and it is either ignored or actively opposed.
Keywords: Socio-Political; Gender constructs; Women; Administration; Neutral Management